(untitled) (Journal of Naval Architecture and Marine Engineering, 2024)
Density of motile microorganisms shows a dynamic character in alleviating and monitoring the momentum, thermal and solutal boundary layers. In sight of this, we examined the flow characteristics on the suspensions of motile microorganisms in the Casson nanofluid due to stretching of a sheet. The stimulus of thermic heat, irregular heat sink or source, thermophorsis and Brownian motion are studied. The flow is laminar and time dependent. The combined influence of heat and mass transfer features are investigated. The velocity slip boundary condition is deemed to investigate the flow features. The modelled equations are highly coupled and nonlinear. So, analytical solution for this model is not possible. Hence, we presented a numerical solution. Suitable similarities are pondered to metamorphose the original PDEs into ODEs and then solved by utilizing R.K. based shooting technique. Influences of varied parameters on the flow fields are discussed in detailed with the aid of graphs and also presented via table. Simultaneous elucidations are bestowed for both Newtonian and non-Newtonian fluids. It is depicted that an enhancement in the thermophoresis parameter results an enhancement in the heat thereby a reduction in concentration. Further, it is characterised that bio convection Lewis number and Peclet number have a reducing behaviour of density of motile microorganisms. Journal of Naval Architecture and Marine Engineering, 21(1), 2024, P: 79- 86